Quantum Teaching Learning Model Assisted Interactive Media: Does it affect Students' Higher Order Thinking Skill? - Mohammad Naufal Fahmi; Putu Sudira; Lucky Al Hafzy (Universitas Pendidikan Ganesha, 2022)
The Freedom to Learn curriculum requires vocational students to have high-order thinking skills, so a model, method, and teaching strategy are needed for teachers. Inappropriate learning models have an impact on students' low thinking abilities. This study aims to analyze the effect of the quantum teaching-learning model on students' higher-order thinking skills. This study uses a quantitative research method with a quasi-experimental research type and a two-group-pretest-posttest research design. The sample of this research is 40 students. The representatives from both classes were randomly selected using the cluster random sampling technique. The method used in collecting data tests higher-order thinking skills. The instrument used in collecting data is a test in the form of description questions. The technique used to analyze the information is statistical inference. The data analysis results show a significant effect of using the quantum teaching model assisted by interactive media on students' higher-order thinking abilities. It was concluded that using the quantum teaching model assisted by interactive media can improve students' higher-order thinking skills.